Reoxygenation of the Hypoxia in the East China Sea: A Ventilation Opening for Marine Life - Chen, Chung-Chi; Ko, Dong S.; Gong, Gwo-Ching; Lien, Chun-Chi; Chou, Wen-Chen; Lee, Hung-Jen; Shiah, Fuh-Kwo; Huang, Yu-Sin Wita (Frontiers in Marine Science, 2022)
Hypoxia and upwelling co-occurred in the summer, and the well-mixed water often reaches the subsurface in the East China Sea (ECS), especially off the Changjiang River estuary. The impact of upwelling on the hypoxia and, therefore, on the ECS ecosystem is not well evaluated. This study demonstrates several positive and negative effects of upwelling on hypoxia and its impact on the ecosystem. With upwelling, hypoxic water expands with a lower pH but has high regenerated nutrients and fugacity of CO2 (fCO2) up to 5–10 m below the surface, which are normally confined to the near-bottom water. It suggests that this upwelling shoaled its hypoxic and acidified bottom water to the subsurface water. This upwelled high nutrient water could, however, provide and enhance phytoplankton growth in this region. On one occasion in August 2014, upwelling reached and outpoured to the surface and lasted for 3 weeks, with the area of coverage ranging from 326.8 to 24,368.0 km2. During this event, the water was mixed thoroughly throughout the water column, with high concentrations of nutrients, chlorophyll a, and slightly undersaturated dissolved oxygen but saturated fCO2, alongside a normal pH. This event may have served as an important conveyor belt from the ocean to the atmosphere for the regenerated CO2. It also provided a productive and suitable environment for marine life and ventilation to alleviate low-oxygen stress in this hypoxic but upwelling region in the ECS.